Technical and Professional Writing Genres A Study in Theory and Practice - Beilfuss, Michael; Peterson, Katrina; Bettes, Staci (Open textbook library., 2019)
This modern, open-source guide to technical and professional writing explores workplace composition through theoretical and practical applications. Discussions of multiple writing genres will assist you in understanding how to apply for jobs, how to compose clear and precise business communications once the job has been acquired, and how to create documents -- such as proposals and reports -- that will be instrumental in helping to advance your career.